Clinical characteristics and outcomes with specific BRAF and NRAS mutations in patients with metastatic melanoma. Issue 21 (6th August 2013) - Bucheit, Amanda D.; Syklawer, Erica; Jakob, John A.; Bassett, Roland L.; Curry, Jonathan L.; Gershenwald, Jeffrey E.; Kim, Kevin B.; Hwu, Patrick; Lazar, Alexander J.; Davies, Michael A.
<x xml:space="preserve">Abstract</x> BACKGROUND Hotspot mutations in BRAF and NRAS are the most common somatic events in patients with melanoma. These mutations occur at highly conserved residues, but include several different substitutions. To determine whether specific mutations are clinically important to differentiate, tumor characteristics and clinical outcomes were compared among patients with advanced melanoma with 1) BRAF V600E versus V600K mutations and 2) NRAS exon 1 versus exon 2 mutations. METHODS Retrospective clinical and pathologic data were collected for patients with advanced melanoma with BRAF or NRAS mutations. The demographics, tumor characteristics, and clinical outcomes of the patients were compared to identify significant mutation‐specific associations. RESULTS Among 302 patients with activating BRAF mutations, 76% had BRAF V600E and 24% had V600K substitutions. Compared with V600E, the presence of a V600K mutation was significantly associated with older age (median, 60.0 years vs 44.7 years; P < .001), male sex (80% vs 59%; P = .001), head/neck primary tumor location (30% vs 15%; P = .0026), shorter interval to stage IV disease (0.98 years vs 2.8 years; P = .015), and a shorter overall survival from the time of diagnosis of stage IV disease (median, 2.44 years vs 1.25 years; hazards ratio, 1.68 [P = .014]). Comparison of 136 patients with NRAS exon 1 (18%) and exon 2 (82%) mutations found an association with primary tumor histology (P = .0096) only. CONCLUSIONS The presence of different substitutions at BRAF V600 correlates with patient demographics, tumor characteristics, and prognosis. These findings demonstrate the presence of mutation‐specific clinical differences between different BRAF genotypes in patients with melanoma, and support the incorporation of this information in patient evaluation and clinical trial design. Cancer 2013;119:3821–3829. © 2013 American Cancer Society.